(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article explores the profound influence of cultural contexts on the interpretation and comparison of literary works across cultures. Literature, as a product of its socio-historical milieu, reflects the values, beliefs, and traditions of its originating society. This study examines how cultural frameworks shape themes, characters, and narrative techniques, and highlights the challenges of cross-cultural literary comparisons. Examples from diverse traditions, such as Western individualism versus Eastern collectivism and postcolonial critiques of identity, underscore the complexity of cultural interpretations. By adopting a contextual approach, readers and scholars can enhance their appreciation of literary diversity and foster a deeper understanding of universal human experiences.